Wearable devices and privacy risks: a literature review - Taco Jimenez, Angelo Rodrigo (2022)
Currently, the use of wearable devices is booming: both children and adults have incorporated this type of device in addition to cell phones into their day-to-day lives, which today are another extension of the human being. This research reviews what wearable devices are, their use, and the risks they imply for the user in terms of privacy and security. The risk identification and control methodology was chosen from the results of a scoping review in the relevant literature.